Joint aging and chondrocyte cell death - Grogan, Shawn P (2010)
Articular cartilage extracellular matrix and cell function change with age and are considered to be the most important factors in the development and progression of osteoarthritis. The multifaceted nature of joint disease indicates that the contribution of cell death can be an important factor at early and late stages of osteoarthritis. Therefore, the pharmacologic inhibition of cell death is likely to be clinically valuable at any stage of the disease. In this article, we will discuss the close association between diverse changes in cartilage aging, how altered conditions influence chondrocyte death, and the implications of preventing cell loss to retard osteoarthritis progression and preserve tissue homeostasis.